Humanitarianism and migratory control: Refuge, medical care, and labor migration - Clavijo, Janneth (2019)
This article reviews the relationship between humanitarianism  and migratory control in international migration policies in Argentina. We  analyze the processes of ambivalent categorization of migrant subjects as  victims and/or threats, through three humanitarian categories that appear  in the regulation of international migrations: refugees, migrants undergoing  medical treatment, and labor migrants. The methodology employed is  qualitative and analyzes: statements of international organizations; national  regulatory frameworks related to migration, refuge, and the transplantation  of organs and tissues; institutional discourses; laws; official reports; and  public commentaries by government officials.